Terminology Analysis of Famous Quotations Translation into Indonesian Language: Penelitian - Susi Septaviana Rakhmawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The paper examines the terminology used in famous quotations and their translation, focusing on their cultural significance and contextual meanings. For this purpose, we built a 70,000-word parallel corpus using Sketch Engine from the English quotes and their Indonesian translations. The data used for this paper were carefully selected from one of 12 translation cycles conducted over two weeks, in which 15 students translated 250 quotes each. University teachers acted as editors, and the finalized translations were published in the online dictionary application LINE. The findings suggest that the meanings of culture-bound terms in famous quotations are deeply rooted in their cultural contexts and historical contexts, reflecting the backgrounds of their original authors. Eight particularly noteworthy terms were analyzed in dept, demonstrating the challenges faced in translation. The study identified Direct Equivalent and Direct Loan as the most frequently used strategies, indicating a tendency to preserve the original nuances and metaphorical meanings of the source language quotations. These findings highlight the complexity of translating culturally embedded expressions and emphasize the need for a balance between fidelity to the source text and comprehensibility for the target audience